Prevalence and molecular characterization of enteropathogenic Escherichia coli isolated from table eggs in Mansoura, Egypt - Elafify, Mahmoud; Elsherbini, Mohammed; Abdelkhalek, Adel; Al-Ashmaw, Maha (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: This study was designed to assess the contamination of enterovirulent Escherichia coli with table eggs at Mansoura, Egypt. Materials and methods: A total of 100 commercially available table eggs were randomly collected from various groceries and supermarkets at Mansoura, Egypt. The samples were screened for the presence of E. coli through conventional bacteriological and biochemical analyses followed by confirmation by polymerase chain reaction. Results: Overall, 18% (n=18/100) samples were found to be contaminated with one or more E. coli isolates. All possible E. coli colonies (n=52) appeared on MacConkey agar plates during the screening process were picked for further analysis. Among the 52 suspected isolates, 24 were confirmed as E. coli, which were further serotyped using polyvalent E. coli antisera. In this study, 9 different E. coli serotypes namely O78, O114, O2, O44, O1, O125, O128, O124 and O26 were identified. Out of these 9 serological strains, 5 (O78, O2, O44, O125, O124 and O26) were positive for eae gene, and 3 (O44, O1 and O128) were positive for stx2 gene. Two serological strains (O44 and O1) were positive for both stx1 and eae genes, while O125 and O114 were positive for stx2 and eae genes. Two strains (O78 and O128) were found to be positive for all three genes (stx1, stx2 and eae). Conclusion: Ensuring hygienic measures can effectively reduce the microbial load from table eggs. http://dx.doi.org/10.5455/javar.2016.c123